Spinal cord injury: Current trends in acute management - C.Y. Adegeest; N. Moayeri; S.P.J. Muijs; P.V. ter Wengel (Brain and Spine)
Introduction: Traumatic spinal cord injury (tSCI) is a profoundly debilitating condition necessitating prompt intervention. However, the optimal acute treatment strategy remains a subject of debate. Research question: The aim of this overview is to elucidate prevailing trends in the acute tSCI management. Material and Methods: We provided an overview using peer-reviewed studies. Results: Early surgical treatment (<24h after trauma) appears beneficial compared to delayed surgery. Nonetheless, there is insufficient evidence supporting a positive influence of ultra-early surgery on neurological outcome in tSCI. Furthermore, the optimal surgical approach to decompress the spinal cord remains unclear. These uncertainties extend to a growing aging population suffering from central cord syndrome (CCS). Additionally, there is a paucity of evidence supporting the beneficial effects of strict hemodynamic management. Discussion and Conclusion: This overview highlights the current literature on surgical timing, surgical techniques and hemodynamic management during the acute phase of tSCI. It also delves into considerations specific to the elderly population experiencing CCS.